The role of culture in a successful knowledge-creation and sharing in higher academic institution– survey/questionnaire - Ahmed Mohamed, Fatima; Fakhri, Nurul Fahimah; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
The purpose of this paper is to contribute to the limited previous research on the role of culture in knowledge creations and knowledge sharing within higher education’s institutions knowledge by examines the role of culture and also by identifying the factors that contributed to the successfulness of the creations and sharing of the knowledge. Design/methodology/approach A questionnaire-based survey was used to gather a side view of university academics’ lecturers and students of International Islamic university Malaysia (IIUM) view, attitudes, perception and intentions toward the culture of knowledge creations and knowledge sharing and related factor, including 35 Responses were received from International Islamic university Malaysia that has a lot of faculties and departments in a university, eight faculties were selected for the study.All items were measured using five-point scales in which 1 “strongly disagree’’ and 5 “strongly agree’’, with the exception of the initial section on Good practices of Knowledge creation and knowledge Sharing In this case a space provided in the form for the respondent to give their feedback. In addition, the questionnaire included a contextual question related to the types of information that academics share, and demographic data including: university, department, length of time in universities (within current department, and also total career-length), position, and gender. The finding The responses toward practicing the culture of KC and KS are varied based on the finding. However, positive feedback on demonstrating those good practices from the respondents to accomplish the status of excellence for IIUM is received. KC and KS are believed as the dynamic elements contributed towards the excellent performance. The KC is a research focus based while KS refers to the re-use of existing for advanced commitments.